A comparative study on the mixture proportions and properties of high performance self-compacting concrete with fly ash, silica fume and metakaolin as mineral admixtures - Karjinni, Vilas V.; Anadinni, Shrishail B. (Journal of Structural Engineering, 2025)
In this experimental work, a mix design for Self-Compacting Concrete (SCC) has been carried out following Nan-Su method.1 The flow properties such as passing ability, filling ability, and segregation resistance2 were evaluated by conducting various tests by varying the dosage of super plasticizer and viscosity modifying admixture (VMA) with fly ash, silica fume and metakaolin as mineral admixtures. Following Nan-Su method for the mix proportions of SCC for M20, M30, M40 and M50 were arrived. Mechanical properties viz. compressive strength, split tensile strength and flexural strength were carried out on cubes, cylinders and beam specimen, respectively. It has been observed from the test results; the quantity of cement was found to be insufficient to get the required strength for all the above said grades and some trials have been made to increase the cement quantity by reducing the mineral admixtures to arrive required strength for normal grade of SCC. The comparative studies have been made on compressive strength, tensile strength, flexural strength, young’s modulus, Poisson’s ratio and density of concrete and are determined after 7 and 28 days curing. Comparing the mechanical properties with conventional concrete laid out some conclusions. Also an attempt has been made to incorporate some suggestions in the Nan-Su method for the normal grades (M20 to M50) of Self-Compacting Concrete.